Analisis Penilaian Mahasiswa terhadap Media Pembelajaran Jobsheet Praktik Proteksi Tenaga Listrik Menggunakan Software Ecodial - Nur Aida Puspa Dewi; Eko Swi Damarwan; Alex Sandria Jaya Wardhana (Journal on Education, 2020)
This study aims to analyze student assessments of the jobsheet learning media for Electrical Power Protection Practice based on Ecodial software. The research employs the Research and Development (R&D) method using the ADDIE model. The jobsheet is designed to enhance students' understanding and skills in low-voltage distribution network protection. Data were obtained through questionnaires measuring the feasibility, ease of use, and benefits of the learning media. The results indicate highly positive evaluations, with an average score of 87% for feasibility, 85% for ease of use, and 90% for benefits. The jobsheet based on Ecodial software has proven effective in helping students comprehend technical concepts, increasing motivation for independent learning, and developing analytical skills. Based on these findings, this media is deemed effective in supporting Electrical Power Protection Practice learning and can serve as a reference for developing technology-based instructional media in the field of electrical engineering.